2001
DOI: 10.1128/jvi.75.17.8224-8239.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Repeated Open Reading Frames, ORFs 63 and 70 and ORFs 64 and 69, of Varicella-Zoster Virus

Abstract: Varicella-zoster virus (VZV) open reading frame 63 (ORF63), located between nucleotides 110581 and 111417 in the internal repeat region, encodes a nuclear phosphoprotein which is homologous to herpes simplex virus type 1 (HSV-1) ICP22 and is duplicated in the terminal repeat region as ORF70 (nucleotides 118480 to 119316). We evaluated the role of ORFs 63 and 70 in VZV replication, using recombinant VZV cosmids and PCR-based mutagenesis to make single and dual deletions of these ORFs. VZV was recovered within 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 52 publications
3
94
1
Order By: Relevance
“…These experiments demonstrated that VZV spreads efficiently between neural cells in vivo, without changing cellular morphology or expression of neural cell proteins, including hNCAM, hGFAP, and ␤-tubulin III. VZV gene expression in neural cells differed dramatically from VZV infection of epidermal and dermal cells in human skin in vivo, which is associated with cell destruction and release of infectious virions (20)(21)(22)(23)(24). IE62, the major viral transactivating protein and an important component of the virion tegument (38,39), was restricted to the nuclei of neurons and glial cells, whereas IE62 localized to the cytoplasm of infected skin cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These experiments demonstrated that VZV spreads efficiently between neural cells in vivo, without changing cellular morphology or expression of neural cell proteins, including hNCAM, hGFAP, and ␤-tubulin III. VZV gene expression in neural cells differed dramatically from VZV infection of epidermal and dermal cells in human skin in vivo, which is associated with cell destruction and release of infectious virions (20)(21)(22)(23)(24). IE62, the major viral transactivating protein and an important component of the virion tegument (38,39), was restricted to the nuclei of neurons and glial cells, whereas IE62 localized to the cytoplasm of infected skin cells.…”
Section: Discussionmentioning
confidence: 99%
“…NOD-SCID mice transplanted with human neurosphere cells (StemCells Inc.) were inoculated with VZV-infected human melanoma cells at 4-6 months after transplant. Viruses tested were pOka, live attenuated vOka (Merck), and rOka⌬70, a deletion mutant with only one copy of the gene encoding IE63 (24). Melanoma cells were grown in tissue culture medium (DMEM, GIBCO) supplemented with heat-inactivated FCS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations